Olfactory Loss and Brain Connectivity after COVID-19: Structural Follow-Up at One Year - Fabrizio Esposito; Mario Cirillo; Rosa De Micco; Giuseppina Caiazzo; Mattia Siciliano; Andrea G. Russo; Caterina Monari; Nicola Coppola; Gioacchino Tedeschi; Alessandro Tessitore (Neural Plasticity)
The structural connectivity from the primary olfactory cortex to the main secondary olfactory areas was previously reported as relatively increased in the medial orbitofrontal cortex in a cohort of 27 recently SARS-CoV-2-infected (COV+) subjects, of which 23/27 had clinically confirmed olfactory loss, compared to 18 control (COV-) normosmic subjects, who were not previously infected. To complement this finding, here we report the outcome of an identical high angular resolution diffusion MRI analysis on follow-up data sets collected in 18/27 COV+ subjects (10 males, mean age±SD: 38.7±8.1 years) and 10/18 COV- subjects (5 males, mean age±SD: 33.1±3.6 years) from the previous samples who repeated both the olfactory functional assessment and the MRI examination after ~1 year. By comparing the newly derived subgroups, we observed that the increase in the structural connectivity index of the medial orbitofrontal cortex was not significant at follow-up, despite 10/18 COV+ subjects were still found hyposmic after ~1 year from SARS-CoV-2 infection. We concluded that the relative hyperconnectivity of the olfactory cortex to the medial orbitofrontal cortex could be, at least in some cases, an acute or reversible phenomenon linked to the recent SARS-CoV-2 infection with associated olfactory loss.